Yeasts identification in microfluidic devices using peptide nucleic acid fluorescence in situ hybridization (PNA-FISH) - Ferreira, AM (2017)
Peptide nucleic acid fluorescence in situ hybridization (PNA-FISH) is a highly specific molecular method widely used for microbial identification. Nonetheless, and due to the detection limit of this technique, a time-consuming preenrichment step is typically required before identification. In here we have developed a lab-on-a-chip device to concentrate cell suspensions and speed up the identification process in yeasts. The PNA-FISH protocol was optimized to target Saccharomyces cerevisiae, a common yeast that is very relevant for several types of food industries. Then, several coinsized microfluidic devices with different geometries were developed. Using Computational fluid dynamics (CFD), we modeled the hydrodynamics inside the microchannels and selected the most promising options. SU-8 structures were fabricated based on the selected designs and used to produce polydimethylsiloxane-based microchips by soft lithography. As a result, an integrated approach combining microfluidics and PNA-FISH for the rapid identification of S. cerevisiae was achieved. To improve fluid flow inside microchannels and the PNA-FISH labeling, oxygen plasma treatment was applied to the microfluidic devices and a new methodology to introduce the cell suspension and solutions into the microchannels was devised. A strong PNA-FISH signal was observed in cells trapped inside the microchannels, proving that the proposed methodology works as intended. The microfluidic designs and PNA-FISH procedure described in here should be easily adaptable for detection of other microorganisms of similar size.